Translators’ Dilemmas in Translating Poetry: The Case of Gane Todorovski’s Poetry in English - Kolevska, Silvana, Sonja Kitanovska-Kimovska and Daniela Andonovska-Trajkovska (Konstantin Preslavsky University of Shumen, Department of English Studies, 2021)
Poetry translation is considered the most challenging type of translation. Translators are faced with many dilemmas as they work on several different levels simultaneously in an attempt to preserve in the target language as many features of a particular poem as possible. This is not an easily achievable aim, especially, if the poems are products of a poetic mastermind who skilfully juggled with a range of poetic features. The study at hand aims to analyse the treatment that the poetry of one such poetic genius, Gane Todorovski, received when rendered from Macedonian into English. More precisely, given the profound differences between Macedonian and English, the study investigates how specific poetic features such as rhyme, rhythm, sound, tropes, word choice and word order have been handled in the translation. It also tries to provide answers to several common translators’ dilemmas that obligatorily emerge in the process of poetry translation. The study shows that the translators of Gane Todorovski’s poetry have been fully aware of the poetic qualities of the original poems and have made every effort to preserve them in the translation, although some losses were practically unavoidable.
Keywords: translation, poetry, lexis, tropes, rhyme